2021
DOI: 10.1111/ijpo.12880
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as the promising markers of comorbidities in childhood obesity—A systematic review

Abstract: Introduction: Rising child obesity rate creates a need for tools quantifying changes in children suffering from obesity, for purposes of detection or prevention of comorbidities. A candidate for such a role seems to be microRNAs, which in vivo serve as the suppressing factors in gene expression.Objectives: This study aimed at reviewing recent discoveries in this field and concluding directions of research or application of studied molecules.Methods: Repeated browsing of databases and screening of results, led … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Larger cohort studies are needed for the verification of our findings. The miRNA expression in obesity may also be gender-dependent, as shown in previous studies on different ethnicities [ 10 , 51 ]. This needs to be explored further in other populations.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Larger cohort studies are needed for the verification of our findings. The miRNA expression in obesity may also be gender-dependent, as shown in previous studies on different ethnicities [ 10 , 51 ]. This needs to be explored further in other populations.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, microRNAs (miRNAs), well-known for their role in diabetes and its complications [ 8 , 9 ], have shown promise as markers of endothelial dysfunction, type 2 diabetes, metabolic syndrome, and IR in children [ 10 ]. The miRNAs produced by AT depots can affect the metabolism of distant tissues because they are easily transported into the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…95 Two miRNAs, miRNA-199a-5p and miRNA-122, were also significantly overexpressed in children with NAFLD compared with healthy controls. 96 Decreased expression of miRNA-139-5p, miRNA-30b-5p, miRNA-122-5p, and miRNA-422a, and increased miRNA-146b-5p has been observed in obese patients with NAFLD compared with sex, age, and weight-matched controls. 97 Activation of AMPK in hepatocytes stimulates fatty acid uptake and oxidation, while it switches off anabolic pathways, such as the synthesis of glucose, glycogen, and lipids.…”
Section: Human Trialsmentioning
confidence: 99%
“…Tissue and circulating miRNAs were extensively studied in the context of pediatric obesity ( 123 , 124 ) but there are no studies on their pre-pregnancy modulation and effects on the obese phenotype on offspring. A work by López and colleagues showed that two miRNAs associated with inflammation and iron homeostasis (miR-155 and miR-122) were upregulated in sperm cells of obese subjects compared to subjects with normal weight ( 125 ).…”
Section: Pediatric Obesity Epigeneticsmentioning
confidence: 99%